Malaysia : Technical Assistance Report-Government Finance Statistics Mission. (IMF Staff Country Reports; Country Report ;, 2019)
This technical assistance report on Malaysia highlights that the mission aimed to support the Malaysian authorities in improving government finance statistics (GFS) for decision making. The mission reviewed the progress in the implementation of the accounting project to introduce accrual financial reporting standards at the federal government level. The mission identified considerable potential for collaboration between Ministry of Finance (MOF) and Department of Statistics Malaysia (DOSM) with respect to fiscal data collection for other general government sublayers and public nonfinancial corporations. The mission concluded that the general ledger structure is sufficient to produce GFS on both cash and an accrual basis. The mission suggested that collaboration between MOF and DOSM going forward would be necessary to ensure data consistency and to facilitate the explanation of remaining minor differences to users. The mission recommends that the authorities verify the causes for inconsistencies based on recent annual data, and to formally align the collaboration between the institutions.